2017
DOI: 10.5194/amt-10-1689-2017
|View full text |Cite
|
Sign up to set email alerts
|

EPN-Repro2: A reference GNSS tropospheric data set over Europe

Abstract: Abstract. The present availability of 18+ years of GNSS data belonging to the EUREF Permanent Network (EPN, http://www.epncb.oma.be/) is a valuable database for the development of a climate data record of GNSS tropospheric products over Europe. This data record can be used as a reference for a variety of scientific applications (e.g. validation of regional numerical weather prediction reanalyses and climate model simulations) and has a high potential for monitoring trends and the variability in atmospheric wat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 50 publications
4
40
0
1
Order By: Relevance
“…Similar biases have been observed for all other European GNSS reprocessing products during the period of 1996-2014 (Pacione et al, 2017). On the other hand, when processing the ERA-Interim using two different software and methodologies within the GNSS4SWEC Benchmark campaign during May and June of 2013 in Central Europe, and by their comparison to two GNSS reference products based on different processing methods, we observed bias differences within ±0.4 mm in ZTD.…”
Section: Zenith Total Delayssupporting
confidence: 52%
See 1 more Smart Citation
“…Similar biases have been observed for all other European GNSS reprocessing products during the period of 1996-2014 (Pacione et al, 2017). On the other hand, when processing the ERA-Interim using two different software and methodologies within the GNSS4SWEC Benchmark campaign during May and June of 2013 in Central Europe, and by their comparison to two GNSS reference products based on different processing methods, we observed bias differences within ±0.4 mm in ZTD.…”
Section: Zenith Total Delayssupporting
confidence: 52%
“…Comparing the results of the official GOP Repro2 solution (GO4) to those of the legacy solution (GO0) demonstrates an overall improvement of 9 % in terms of accuracy, which corresponds to a similar comparison between the EUREF Repro1 and Repro2 products (Pacione et al, 2017). The improvement is assumed to be even larger (indicated by the coordinate repeatability) since the comparison of tropospheric parameters is limited by a lower quality of reference products derived from NWM data Kačmařík et al, 2017;Bock and Nuret, 2009).…”
Section: Zenith Total Delaysmentioning
confidence: 99%
“…The GPS data were obtained by the Finnish Geodetic Institute and the National Land Survey of Finland as Receiver INdependent EXchange format (RINEX) files and processed in Precise Point Positioning [38] mode using the Global Navigation Satellite System (GNSS)-Inferred Positioning System and Orbit Analysis Simulation Software package GIPSY-OASIS II [39], with a cut-off angle of 3 • . We fixed Jet Propulsion Laboratory (JPL) fiducial-free satellite orbits, clocks, and earth orientation parameters and state-of-the-art processing options to estimate ZTD with a 5-min sampling [40,41]. The Vienna mapping function [42] was applied to the delay of the signal along each satellite-receiver path in order to map it into the zenith direction.…”
Section: Gps-derived Iwv Datamentioning
confidence: 99%
“…The data are processed using the Bernese 5.0 software with a cut-off angle of 3 • and are provided with a temporal resolution of 30 min. Pacione et al [41] evaluated the agreement between the different GPS software packages-Bernese [46], GAMIT [47], and GIPSY-OASIS II [39]-in terms of the ZTD standard deviation. They found that the overall agreement is better than 3 mm before 26 March 2000 and 2 mm thereafter.…”
Section: Instrumentation At the North Slope Of Alaskamentioning
confidence: 99%
“…The GPS station is operated by the Finnish Geodetic Institute and the National Land Survey of Finland. GPS data were obtained as RINEX files and 5 processed in Precise Point Positioning mode using GIPSY-OASIS II and state-of-the-art processing options to derive ZTD with a 5-minute sampling (Pacione et al, 2014;Pacione et al, 2017). The ZTD known as the "tropospheric total delay" by the neutral atmosphere can be expressed as the sum of two components: zenith hydrostatic delay (ZHD) due to hydrostatic gases (mainly oxygen) and ZWD due to water vapour (Elgered, 1993).…”
Section: Gps Datamentioning
confidence: 99%